Unveiling the mechanism of sodium ion storage for needle- shaped ZnxCo3-xO4 nanosticks as anode materials - Islam, Mobinul; Ali, Ghulam; Jeong, Min-Gi; Kim, Hyung-Seok; Choi, Wonchang; Chung, Kyung Yoon; Jung, Hun-Gi (ROYAL SOC CHEMISTRY, 2019)
The interest in the development of micro-nanostructured metal oxides has been increasing recently because of their advantages as electrode materials in energy storage applications. In this study, dandelion-like ZnxCo3-xO4 microspheres assembled with porous needle-shaped nanosticks were synthesized by co-precipitation followed by a post-annealing treatment. The open space between neighboring nanosticks enables easy infiltration of the electrolyte; therefore, each nanostick is surrounded by the electrolyte solution, which ensures proper utilization of the active material during the electrochemical reaction. The dandelion-like ZnxCo3-xO4 hierarchical microspheres exhibit a greatly improved electrochemical performance with a high capacity and good cyclability as anodes for sodium-ion batteries (SIBs). A high initial reversible capacity of 612 mA h g(-1) (at 35 mA g(-1), approximate to 0.04C) is obtained and a capacity of 349 mA h g(-1) is retained after 200 cycles. Meanwhile, the electrode shows a high rate performance with a capacity of 246 mA h g(-1) at 2.0C-rate. The conversion of ZnxCo3-xO4 with Na is followed by ex situ X-ray absorption spectroscopy (XAS) and transmission electron microscopy (TEM) in different sodiation/de-sodiation states during electrochemical cycling. These analyses reveal that Na insertion/extraction is followed by complete reduction/oxidation of both metallic cobalt and zinc. The development of metallic Co and Zn after complete discharge and the formation of Co3O4 and ZnO when the electrode was fully recharged were identified by ex situ TEM analysis. In addition, the ZnxCo3-xO4 anode demonstrates feasible operation in a full cell by pairing with a NaNi2/3Bi1/3O2 cathode, affording a sodium-ion battery with an average working voltage of 2.6 V.
Keywords: HIGH-PERFORMANCE ANODE; ENHANCED ELECTROCHEMICAL PERFORMANCE; LITHIUM-ION; LI-ION; BATTERY ANODE; CONVERSION REACTION; RATE CAPABILITY; HIGH-CAPACITY; CARBON; NA